Workability maintenance of water-reducing admixtures in high-performance pastes produced with different types of Portland cement - Matos,Paulo Ricardo de (2021)
ABSTRACT This work evaluated the efficiency and workability manteinance of a polyfunctional (lignosulfonate-based) and a superplasticizer (polycarboxylate-based) admixture in high-performance pastes (water/cement ratios of 0.30, 0.33 and 0.36) produced with two types of Portland cement (one pozzolanic and one high early strength). The workability of the pastes was evaluated by the mini slump test immediately after mixing, and after 20 and 40 minutes. Furthermore, the mechanical strength of pastes with fixed w/c ratio (0.36) and mini slump (130 mm), produced with the different combinations of cements and admixtures, was evaluated. The results showed that the CP IV+lignosulfonate and CP V-ARI+polycarboxylate mixes presented the best workability maintenance over time. The pastes produced with CP V-ARI presented 28-day strengths about 22% higher than those produced with CP IV, for both admixtures. In turn, the lignosulfonate-containing pastes showed strengths about 10% higher than those produced with the polycarboxylate-based admixture. Overall, it was possible to obtain the same workability for high-performance Portland cement pastes produced with both admixtures and cements; however, the workability mantainance and mechanical strength highly depends on the combination of cement and admixture used.